Pengembangan Desain Didaktis Bahan Ajar Materi Pemfaktoran Bentuk Aljabar pada Pembelajaran Matematika SMP - Rizki Wahyu Yunian Putra; Nurwani Nurwani; Fredi Ganda Putra; Nugraha Wisnu Putra (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2017)
The ability to understand a concept in the learning of mathematics is something that is required by each learner. But in fact show that in the learning process, teaching materials used have not trained learners in doing a discovery and learners less active in the learning process. This study aims to produce teaching materials in the form of a didactic design module teaching materials Algebra on Mathematics Subjects for Class VIII Semester 1 Subject material Algebra in SMP Negeri 1 Pakuan Ratu. The teaching materials module with didactic design is a module in the form of a learner's guide which contains information, materials about Algebra, examples of problems as well as exercise questions, in accordance with the problems that natural learners on learning materials, this instructional material is made to petrify participants educated in solving problems on Algebra material. Based on the results of research, Didactic instructional materials developed by researchers deserve to be used according to the validation results of material experts, linguists, education practitioners, media experts, and help learners to learn more independently and comfortable in the learning process as well as learners are very interested in teaching materials (modules) of this didactic design.